Development of a nanostructured electrochemical immunosensor applied to the early detection of invasive aspergillosis - Piguillem Palacios, Sofía Viviana (2018)
The use of a biological marker as an adjunct for screening for invasive aspergillosis (IA) in high-risk patients is attractive, because it is noninvasive and may detect evidence of IA prior to the appearance of clinical signs and symptoms. Galactomannan (GMN) is a polysaccharide cell-wall component that is released by Aspergillus species. In the present work, an electrochemical microfluidic immunosensor for GMN detection was developed. Moreover, copper nanoparticles covered with polyvinylpyrrolidone (CuNPs-PVP) were synthesized, characterized and used in a microfluidic immunosensor based on the use of anti-GMN antibodies as a trapping agent. The concentration of trapped GMN is then electrochemically quantified by HRP-conjugated anti-GMN-antibody. HRP reacted with its enzymatic substrate in a redox process which resulted in the appearance of a current whose magnitude is directly proportional to the concentration of GMN. The immunosensor was validated by analyzing patient samples, and a good correlation with a commercial ELISA was obtained. This microfluidic immunosensor can be applied to the early diagnosis of IA.